Evaluation of the Prudential Principle in Credit Disbursement in Sumenep Regency - Qutsiyah, Khasyiratul; Sihabudin, Sihabudin; Andreassari, Letzia Dessy (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
This study analyzes the implementation of the prudential principle in banking, as mandated by Article 8 of Law Number 10 of 1998 in conjunction with Article 2 of Law Number 7 of 1992, in the context of credit disbursement in Sumenep Regency. The prudential principle serves as a key foundation for maintaining financial stability and mitigating credit risk. The research focuses on three banks operating in the region—Bank Syariah Indonesia (BSI) KCP Sumenep, Bank Jatim KCU Sumenep, and Bank BPRS Bhakti Sumekar and seeks to evaluate how the principle is operationalized, while identifying key barriers and institutional responses. A qualitative method is adopted, using in-depth interviews and observational techniques to gather relevant data. Findings show that each bank has consistently applied the 5C and 3R principles and utilizes the Financial Information Service System (SLIK) from OJK to assess borrower risk. Despite this, several systemic challenges persist. These include inadequate legal enforcement mechanisms against defaulting debtors, limited public financial literacy, and internal organizational pressure related to credit targets. While infrastructural support appears sufficient, the overall impact of the prudential principle on reducing non-performing loan rates remains suboptimal. The study argues for regulatory reforms that embed prudential requirements more firmly within statutory law, rather than leaving them to soft regulations. Additionally, strengthening institutional capacity and enhancing the ethical competence of banking personnel are considered vital steps to reinforce effective credit governance.